(untitled) (Research, Society and Development, 2021)
Metal-ceramic fixed partial dentures (PPF) have been a treatment option widely used by dentists, with significantly high long-term success rates. However, their rates are based on clinical trials conducted under standardized conditions and do not represent clinical realities. Thus, this work aims to emphasize the survival of metalloceramics, through a clinical case of rehabilitation, using Ni-Cr metal alloy and resin-modified glass ionomer cement with a 12-year follow-up. The case was rehabilitated with two posterior five-element PPF with two pontics and five anterior unitary fixed prostheses for the upper arch and two posterior five-element PPF with two pontics for the lower arch. It was concluded that the PFF have a high success rate for a long period of follow-up, and their longevity is linked to the correct planning, choice of materials and techniques.